COMPARING FORECASTING METHOD IN THE DREAM CARD MALANG COMPANY USING FORECASTING SEASONAL FORECASTING METHODS - Mochammad Hilmy Tamala Putra; Andre Jesilla Jones; Liem Gai Sin (AIBPM Publisher, 2018)
This paper examines the aspects of forecasting method of production that are efficient and effective within a book industrial. The purposes of the paper are to searching and comparing the forecasting analysis methods of production on Dream Card Factory Malang which included in a book industry along with analyzing the factors which influence production in the company. Qualitative data were acquired where-by interviews with the owner of the Dream Card Company Malang or with workers from production sector of the company. Quantitative data were acquired by observing the result of annual production report or quarter production report on the Dream Card Company Malang. The contribution of this paper offers is compatible forecasting method for the Dream Card Company. Keywords – Annual, Compatible, Forecasting Method, Influence, Quarter